2018
DOI: 10.1111/apa.14382
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular impact of intravenous caffeine in preterm infants

Abstract: This study highlights potential elevation in autonomic nervous system responsiveness following caffeine administration reflected in both heart rate and blood pressure systems. The observed increase in pulse pressure variability may have implications for caffeine administration to infants with potentially impaired cerebral autoregulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…DFA1 has not previously been studied in infants with CCHD. Researchers have reported significant reductions in DFA1 in premature infants during conditions that would be expected to increase sympathetic responses, such as following delivery of loading doses of caffeine (Huvanandana, Thamrin, McEwan, Hinder, & Tracy, 2018) and rewarming following therapeutic hypothermia (Massaro et al, 2017). Findings of DFA1 trajectories in cardiac-SSC infants similar to TD infants support further studies with sufficient sample sizes.…”
Section: Discussionmentioning
confidence: 99%
“…DFA1 has not previously been studied in infants with CCHD. Researchers have reported significant reductions in DFA1 in premature infants during conditions that would be expected to increase sympathetic responses, such as following delivery of loading doses of caffeine (Huvanandana, Thamrin, McEwan, Hinder, & Tracy, 2018) and rewarming following therapeutic hypothermia (Massaro et al, 2017). Findings of DFA1 trajectories in cardiac-SSC infants similar to TD infants support further studies with sufficient sample sizes.…”
Section: Discussionmentioning
confidence: 99%
“…Our results regarding the effect of caffeine on HR and HRV are in accordance with the study of Ulanovsky et al who also didn't show any impact of caffeine (applied in a loading dose 15-20 mg/kg/day, followed by a maintenance dose of 5-10 mg/kg/day) either on the HR or HRV in premature newborns. Yet, their sample may not be comparable to ours, as the newborns in their study [1] as well as in Huvanandana's [3] were younger than our newborns (gestational age 30.3 ± 2.5 weeks and 27.0 (23.6-33.3) weeks compared to 34 ± 5 weeks in our study) and also had signi cantly lower birth weight (1397 ± 458 g and 934 (552-2100) g compared to 2353 ± 914 g in our study) [1,3]. On the other hand, Huvanandana et al who compared the results of the linear and non-linear measurements of HRV in preterm newborns prior to and two hours after a loading caffeine dose, reported an increased HRV after caffeine administration when using non-linear, but not when using linear modelling, as it was analysed in our study.…”
Section: Discussionmentioning
confidence: 73%
“…On the other hand, Huvanandana et al who compared the results of the linear and non-linear measurements of HRV in preterm newborns prior to and two hours after a loading caffeine dose, reported an increased HRV after caffeine administration when using non-linear, but not when using linear modelling, as it was analysed in our study. They suspected that linear metrics might not adequately capture potentially altered dynamics in the HR control [3]. Moreover, the in uences of caffeine on the heart and the activity of ANS seem controversial as caffeine has also been shown to increase the HF component of HRV in adults, apparently increasing PNS activity [21,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, Huvanandana et al. evaluated the cardiovascular impact of intravenous caffeine and found that caffeine was likely to increase the responsiveness of the autonomic nervous system. Meanwhile, Seppä‐Moilanen et al.…”
Section: Caffeine and The Neonatal Heart And Lungsmentioning
confidence: 99%